Pengaruh Citra Merek Melalui Sikap Konsumen Terhadap Niat Beli Ulang Pada Produk Busana Muslim Zoya di Surabaya - Ain, Nurul; Ratnasari, Ririn Tri (Jurnal Ekonomi Syariah Teori dan Terapan, 2015)
This study aims to determine the effect of brand image to re-purchase intention throughÂ attitude of consumers to the brand in the Zoyaâs Muslim fashion products in Surabaya.This sudy collects primary data from the questionere with 30 sample. The sample is theÂ consumer of Zoyaâs products in Surabaya. This study utilizes Consumer characteristics whoÂ have ever made a purchase Zoyaâs products in Surabaya within the past year. The samplingÂ technique is accidental and purposive sampling.This study utilizes quantitative approach path analysis technique (path analysis).Endogenous variables is re-purchase intention, whereas exogenous variables is brand imageÂ and intervening endogenous variable is the attitude of consumers to the brand image. TheÂ results indicates that the brand image has a positive and significant impact to the consumerÂ attitudes on Zoyasâs Muslim fashion brand. Other results shows that a significant influence onÂ consumer attitudes and re-purchase intention . Then, the brand image is also has positiveÂ and significant impact on re-purchase intention on the Zoyaâs Muslim fashion in Surabaya.Â Based on these findings, Zoya Surabaya branch should maintain and enhance the brand Â image of Zoya and positive attitudes of consumers towards the Muslim fashion Zoya so as toÂ improve on the consumers purchase intention on products Moslem Zoya. For the furtherÂ research, it will be better by adding a moderator variables such as the level of religiousÂ knowledge that will get an idea whether the moderator variables will weaken or increase theÂ influence of consumer attitudes to re-purchase intention of consumers on Zoyasâs Muslimfashion brand.